A swept-source optical coherence tomography study of the spectrum of laser pointer maculopathy - Magdy Moussa; Mahmoud Leila; Mohammed Fotouh Elashri; Ahmed Osama Hashem (International Journal of Retina and Vitreous)
Abstract Background To evaluate the efficacy of swept-source optical coherence tomography (SS-OCT) in detecting the clinical spectrum of macular microstructure changes secondary to laser pointer injury (LPI), including their response to therapeutic intervention. Methods: A retrospective study, including consecutive patients with LPI. Inclusion criteria were visual symptoms and biomicroscopic, OCT, and fundus fluorescein angiography (FFA) features of LPI. We used the SS-OCT for imaging and the swept-source optical coherence tomography angiography (SS-OCTA) to confirm or exclude the diagnosis of a choroidal neovascular membrane (CNV). We used FFA to confirm the diagnosis of a CNV whenever SS-OCT and SS-OCTA images were insufficient to establish its presence. The outcome measures were the morphological features in the macula secondary to LPI and the response of CNV to aflibercept. Results: The study included 31 eyes of 22 patients. Ten patients (45%) were ≤ 15 years old. Laser pointer maculopathy (LPM) was bilateral in 9 patients (41%). The mode of injury was self-inflicted in 14 patients (64%). Central scotoma was the most common symptom reported by the patients. The mean baseline best-corrected visual acuity (BCVA) was 20/50. The mean follow-up period was 9.6 months. The mean final BCVA was 20/40. Acute stages of LPM were characterized by focal or diffuse disruption of the outer retinal layers, subretinal hyperreflective mound, anvil-shaped lesion, or the angular sign of Henle fiber layer hyperreflectivity (ASHH). The features of chronic stages included secondary CNV or macular holes. CNV and macular hole were common features in both acute and chronic stages. The most common LPI-induced macular lesion was retinal pigment epithelium (RPE) changes. Type II CNV developed in three eyes (10%). Conclusion: SS-OCT depicted a characteristic morphological profile of LPM in the acute and chronic stages. SS-OCTA is a non-invasive and reproducible complementary tool in detecting secondary CNV and monitoring its response to therapy.